2020
DOI: 10.1182/bloodadvances.2020003314
|View full text |Cite
|
Sign up to set email alerts
|

Determining the recommended dose of pacritinib: results from the PAC203 dose-finding trial in advanced myelofibrosis

Abstract: PAC203 is a randomized dose-finding study of pacritinib, an oral JAK2/IRAK1 inhibitor, in patients with advanced myelofibrosis who are intolerant of or resistant to ruxolitinib. Patients were randomized 1:1:1 to pacritinib 100 mg once per day, 100 mg twice per day, or 200 mg twice per day. Enhanced eligibility criteria, monitoring, and dose modifications were implemented to mitigate risk of cardiac and hemorrhagic events. Efficacy was based on ≥35% spleen volume response (SVR) and ≥50% reduction in the 7-compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 28 publications
(26 reference statements)
1
43
0
Order By: Relevance
“…The PACIFICA study (NCT03165734), which is recruiting patients with MF and severe thrombocytopenia (platelet counts < 50.10 9 /L at baseline), will evaluate pacritinib as first- or second-line treatment after JAK inhibitor versus physician’s choice, that may include low-dose ruxolitinib. The phase 2 PAC203 study has demonstrated that the dose of 200 mg twice daily of pacritinib provided better response than low dosages with no excess of grade 3 events [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PACIFICA study (NCT03165734), which is recruiting patients with MF and severe thrombocytopenia (platelet counts < 50.10 9 /L at baseline), will evaluate pacritinib as first- or second-line treatment after JAK inhibitor versus physician’s choice, that may include low-dose ruxolitinib. The phase 2 PAC203 study has demonstrated that the dose of 200 mg twice daily of pacritinib provided better response than low dosages with no excess of grade 3 events [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This phase 2 trial demonstrated that 200 mg BID was the most effective dose resulting in SVR 35% rates of 9.3% in this previously JAK inhibitor-treated population. Importantly, in patients with platelets below 50 × 10 9 /L, the SVR 35% rate was 16.7% and when considering only evaluable patients in this subgroup, 30.8% achieve an SVR 35% [ 26 ]. Given promising activity of pacritinib in thrombocytopenic patients, a phase III trial, PACIFICA, is currently accruing MF patients with a platelet count less than 50 × 10 9 /L (NCT03165734) and limited or no prior ruxolitinib exposure and randomizing them to pacritinib 200 mg twice daily versus physician’s choice.…”
Section: Jak Inhibitorsmentioning
confidence: 99%
“…Spleen responses were more common in patients treated with 200 mg BID and symptom responses occurred with similar frequency across all dose levels. [64] Therefore, a dose of 200 mg BID has been selected for a randomized phase 3 study of patients with MF with severe thrombocytopenia, disease-related symptoms, and splenomegaly (PACIFICA; NCT03165734). [65] In this study that aims to enroll 348 patients, participants will be randomized to either pacritinib or physician's choice of a single-agent therapy with a primary endpoint of spleen response at 24 weeks.…”
Section: Jak Inhibitors In Development Pacritinibmentioning
confidence: 99%